A case of purpura fulminans secondary to transient protein C deficiency as a complication of chickenpox infection - (:unkn) unknown (TURKISH J PEDIATRICS, 2002)
Purpura fulminans is a rare but dramatic disease which occurs most commonly during or after an infection. It is characterized by extensive involvement of the skin and extremities and involvement of visceral organs. Purpura fulminans, when occurring after a viral infection such as varicella, is usually characterized by purpuric lesions involving the trunk, usually with sparing of the visceral organs. In this report we describe a child with purpura fulminans due to a transient protein C deficiency as a complication of chickenpox infection. A seven-year-old girl developed bruise-like lesions on her extremities on the fifth day after eruption of varicella exanthem. She had no previous history of bleeding tendency or thrombosis. Family history was also negative. On the seventh day of her illness she was admitted to Marmara University Hospital with widespread echymotic an partially crusted chickenpox lesions. CBC, urinalysis and blood chemistries were within normal limits. She had a prolonged aPT and apt with low serum fibrinogen and high D-dimers suggestive disseminated intravascular coagulation (DIC). Protein C activity was low. Punch skin biopsy was consistent with purpura fulminans. She was treated with heparin and fresh frozen plasma which helped her to recover clinically as well as hematologically. She was discharged with still low protein C activity that returned to normal by the next follow-up visit.
Keywords: purpura fulminans; protein C deficiency; chickenpox; S DEFICIENCY; SKIN NECROSIS; CHILDREN; MENINGOCOCCEMIA; ANTIBODIES